The logic behind evolution of economic systems under uncertainty and the choice of a socialist market economy - Zhen Qiao (China Political Economy)
Purpose – This paper aims to determine the status of the socialist market economy through a logical analysis of the evolution of economic systems in human society. Design/methodology/approach – This paper presents an analysis of uncertainty and the functions performed by different economic systems in managing and resolving it, thereby explaining the evolutionary rationale behind economic system evolution. Findings – Firstly, the socialist market economy empowers the market to play a decisive role in resource allocation, which serves as the foundation for activating individuals' motivation to engage in economic activities. Secondly, the socialist market economy adheres to the basic socialist economic system, which is the basis for the socialist market economy to stabilize the economy and society or to address the risk of economic uncertainty that may trigger macro-level inconsistencies in economic operations. Thirdly, the advantages of a socialist market economy in adapting to economic uncertainties do not arise spontaneously and must be exerted through continuous improvement of the socialist market economy. Originality/value – The innovation of this paper lies in introducing uncertainty to clarify the logic behind the evolution of economic systems in human society and explaining the typical significance of the socialist market economy and its advantages in accommodating and resolving uncertainty.